Actin Bundle Nanomechanics and Organization Are Modulated by Macromolecular Crowding and Electrostatic Interactions - Castaneda, Nicholas; Feuillie, Cecile; Molinari, Michael; Kang, Ellen Hyeran (Frontiers in Molecular Biosciences, 2021)
The structural and mechanical properties of actin bundles are essential to eukaryotic cells aiding in cell motility and mechanical support of the plasma membrane. Bundle formation occurs in crowded intracellular environments composed of various ions and macromolecules. Although the roles of cations and macromolecular crowding in the mechanics and organization of actin bundles have been independently established, how changing both intracellular environmental conditions influence bundle mechanics at the nanoscale has yet to be established. Here we investigate how electrostatics and depletion interactions modulate the Young’s modulus and height of actin bundles using atomic force microscopy. Our results demonstrate that cation- and depletion-induced bundles display an overall reduction of relative Young’s modulus dependent on either cation or crowding concentrations. Furthermore, we directly measure changes to cation- and depletion-induced bundle height indicating bundles experience alterations to filament packing supporting reduction to relative Young’s modulus. Taken together, our work suggests that electrostatic and depletion interactions may act counteractively impacting actin bundle nanomechanics and organization.